ANALISIS PENGARUH ADOPSI ISPO TERHADAP PERBAIKAN KINERJA PENGELOLAAN LINGKUNGAN DAN PERUBAHAN SOSIAL EKONOMI MASYARAKAT - M. Imam Arifandy; Hariyadi Hariyadi; Soeryo Adiwibowo (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Indonesian Sustainability Palm Oil (ISPO) is requirement for palm oil private business in the effort to preserve the environment, increase economic activities, and social activities of the community. The environmental management conducted by the company is analyzed by qualitative descriptive approach by comparing the condition of management before and after the implementation of ISPO. Measurement of the influence of CSR program as implementation in ISPO to the changing socio-economic condition of the community is done by quantitative approach with simple linear regression statistic analysis method. This study aims, first to analyze eh impacts of ISPO adoption in improving the environmental management performances of the company, second to analyze the influence of CSR program to the socio-economic condition of the community. ISPO implementation impacts on; first, environmental benefits obtained by the company include; (1) increase discharge and quality of processed wastewater for Land Application, (2) reduce of CO2 emissions 2.134.299 tons/year; (3) reduce of air emission and noise level in plant area; (4) reduce case of land fires and work accidents, (5) improve groundwater quality and Kandis river water quality, (6) improve of worker's capability and welfare. Second, the economic benefits obtained by the company, including; (1) increase of CPO production by 827 tons/year, and PKO production by 75 tons/year, (2) cost savings IDR 98.228.703/year from IPAL management improvements, and (3) Increase of company's revenue from selling hazardous waste to third party by IDR 343.734.000/year. Third, CSR program positively increase of community's income, education improvement of community family member, and better public perception to company.